Meningkatkan Kemampuan Bercerita Melalui Media Buku Cerita Bergambar Kisah Nabi MUhammad Saw (Seri Kejujuran) Pada Anak Kelompok B RA ABA Bongohulawa - Zaka Afifa; Munirah; Wiwik Pratiwi (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
Storytelling ability is an essential aspect of early childhood language development. However, observations at RA ABA Bongohulawa revealed that most children were not yet able to organize stories coherently, had limited vocabulary, and lacked confidence in speaking. This study aimed to improve children’s storytelling skills while fostering speaking etiquette through the use of an illustrated storybook featuring the story of Prophet Muhammad (peace be upon him), specifically the honesty series. This study employed a Classroom Action Research (CAR) design consisting of two cycles involving 15 children in Group B. The research procedures included planning, action implementation, observation, and reflection. Data were collected through observation, interviews, and documentation, and analyzed qualitatively and quantitatively based on the percentage of learning mastery. The findings showed a significant improvement in children’s storytelling skills, increasing from an average of 34.16% in the pre-cycle to 64% in Cycle I, and reaching 89.16% in Cycle II. Improvements were found in indicators such as connecting pictures, organizing story sequences, vocabulary use, speaking fluency, as well as expression and articulation. In addition, the use of prophetic stories contributed to the development of speaking etiquette, including the confidence to tell stories politely, honesty, and children’s self-confidence. The novelty of this study lies in integrating visual media with tarbiyah values in early childhood language learning. Therefore, illustrated storybooks are not only effective in improving storytelling skills, but also serve as a medium for fostering children’s moral character and holistic development.